2000
DOI: 10.1128/aem.66.1.325-331.2000
|View full text |Cite
|
Sign up to set email alerts
|

Production and Comparison of Peptide Siderophores from Strains of Distantly Related Pathovars of Pseudomonas syringae and Pseudomonas viridiflava LMG 2352

Abstract: The production of peptide siderophores and the variation in siderophore production among strains of Pseudomonas syringae and Pseudomonas viridiflava were investigated. An antibiose test was used to select a free amino acid-containing agar medium favorable for production of fluorescent siderophores by two P. syringae strains. A culture technique in which both liquid and solid asparagine-containing culture media were used proved to be reproducible and highly effective for inducing production of siderophores in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 35 publications
3
54
0
Order By: Relevance
“…The siderophore activity (and production) in HS124 increased over a relatively wide range of iron concentrations reaching a peak at 100 µM Fe (III), followed by a sharp decline at concentrations beyond 100 µM. The observed pattern is generally consistent with earlier reports that gradual repression of siderophore production was observed with increasing concentrations (0 to 10 µM) of iron (III) in Pseudomonas syringae (Bultreys and gheysen, 2000), and that total repression of siderophore production by the same species was observed at iron (III) concentration of 100 µM (Laine et al, 1996). However, our findings suggest that Fe (III) requisition by HS124 was considerably higher than those of other siderophore producing bacteria.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The siderophore activity (and production) in HS124 increased over a relatively wide range of iron concentrations reaching a peak at 100 µM Fe (III), followed by a sharp decline at concentrations beyond 100 µM. The observed pattern is generally consistent with earlier reports that gradual repression of siderophore production was observed with increasing concentrations (0 to 10 µM) of iron (III) in Pseudomonas syringae (Bultreys and gheysen, 2000), and that total repression of siderophore production by the same species was observed at iron (III) concentration of 100 µM (Laine et al, 1996). However, our findings suggest that Fe (III) requisition by HS124 was considerably higher than those of other siderophore producing bacteria.…”
Section: Discussionsupporting
confidence: 80%
“…Siderophores produced by Pseudomonas syringae and Pseudomonas viridiflava (Bultreys and Gheysen, 2000), for example, played a vital role in the biocontrol of plant pathogens. Similarly siderophores produced by Pseudomonas fluorescens promoted plant growth via competition for iron (Loper and Henkels, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Siderophores are low molecular weight, high-affinity iron(III) chelators that function as important virulence factors in many bacterial pathogens because of their role in sustaining growth in iron-limited host environments. Synthesis of the siderophore pyoverdin is well documented among fluorescent pseudomonads (41), and the required genes are present in a single cluster in DC3000. Also, a cluster of genes homologous to those required for biosynthesis of the siderophore pyochelin by P. aeruginosa has been found.…”
Section: Ttss and Effectorsmentioning
confidence: 99%
“…A better understanding of the ecological benefits of these pathogens is necessary if efficient methods of biological control are to be developed. Recently, it was shown that an apparently identical fluorescent peptide siderophore is produced by strains belonging to distantly related pathovars of P. syringae and to the closely related phytopathogenic species Pseudomonas viridiflava (7). The spectral characteristics of the molecule differ from those of typical pyoverdins (7), which are the fluorescent peptide siderophores generally produced by saprophytic and opportunistic animal pathogen fluorescent Pseudomonas species (2,4).…”
mentioning
confidence: 97%
“…Recently, it was shown that an apparently identical fluorescent peptide siderophore is produced by strains belonging to distantly related pathovars of P. syringae and to the closely related phytopathogenic species Pseudomonas viridiflava (7). The spectral characteristics of the molecule differ from those of typical pyoverdins (7), which are the fluorescent peptide siderophores generally produced by saprophytic and opportunistic animal pathogen fluorescent Pseudomonas species (2,4). The production of the fluorescent siderophore by P. syringae is activated under conditions that are related to conditions encountered on plant surfaces (7,23,30,42,43).…”
mentioning
confidence: 99%